Preparation of Polyethyleneimine-Grafted Sodium Lignosulfonate Microspheres and Their Methyl Orange Adsorption Performance over a Wide pH Range - Martin, Jessica; Lee , Thomas (Journal of Functional Materials and Applied Engineering, 2024)
Conventional adsorbents fail to meet the demands of green sustainable development, and suffer drawbacks including narrow applicable pH window, high temperature sensitivity and poor regeneration capacity. In this work, polyethyleneimine (PEI) was grafted onto sodium lignosulfonate (LS) via inverse suspension polymerization to synthesize bio-based microspheres (LSMs) capable of adsorbing organic dyes across a broad pH spectrum. A suite of physicochemical characterization techniques, including scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA), was applied to thoroughly examine the synthesized microspheres. Owing to their textured surface topography coupled with a high density of surface amine functionalities, the LSMs demonstrated robust and stable sequestration of methyl orange (MO) across a broad pH spectrum spanning from 3 to 11. Systematic batch equilibrium and kinetic studies were subsequently executed to elucidate the governing parameters influencing the MO uptake capacity of these microspheres. Among the models tested, the measured data were most faithfully reproduced by the combination of the Langmuir isotherm and the pseudo-second-order kinetic equation, from which the monolayer uptake capacity of the adsorbent was determined to peak at 416.03 mg·g⁻¹. Reusability tests further highlighted the durability of the material: over ten rounds of adsorption followed by desorption, more than 98% of the dye could still be eliminated. Spectroscopic evidence gathered from FTIR and X-ray photoelectron spectroscopy (XPS) sheds light on how the dye is captured — rather than relying on a single driving force, the LSM adsorbent binds MO molecules through several non-covalent forces acting in concert, namely electrostatic attraction, hydrogen bonding, π–π stacking, and van der Waals interactions.